The Safety and Efficacy of Cold Atmospheric Plasma as a Novel Therapy: An in vivo Study - Atieh Akbari; Mahdiyeh Bakhtiyari-Ramezani; Dorsa Najari; Mehdi Aziz Mohamadlooha; Afshin Moradi; Mahdis Bayat; Fereshteh Abbasvandi; Batoul Khoundabi; Mohammad Esmaeil Akbari (Middle East Journal of Cancer)
Background: Cold atmospheric plasma (CAP) may reduce bacteria and aid wound healing through reactive oxygen species. Recent trials support CAP for chronic wounds, but its effectiveness is not well-proven. This studyevaluates the efficacy of CAP on wound healing rate.Method: This cross-sectional study was conducted sequentialy to investigate the impact of CAP intervention on wound healing in rats over a period from 2022 to 2023. The study was carried out at the Atomic Energy Organization of Iran.A total number of 16 ratswere divided into three groups based on the duration of CAP exposure: Group 1 (0 minutes), Group 2 (3 minutes), and Group 3 (5 minutes). Continuous variables were reported as mean ± SD. Group differences were analyzed using ANOVA or Kruskal-Wallis. A P-value <0.05 was considered statistically significant.Results: Day zero analysis revealed an absence of acute inflammatory response, with neutrophils consistently absent across all groups. Lymphocytes were predominantly absent, with a mild presence observed in most cases. Granulation tissue was mainly absent, and when present, it exhibited minimal extent. Blood vessel count was mostly below 20 per 10 high-power fields, with a slightly higher count in the 5 minute CAP intervention group. Fibroblasts were mostly absent, and when present, they were found in minimal extent. Ulcers, keloids, and hypertrophic scars were largely absent in all cases. Day seven and fourteen analyses revealed no significant differences between the left and right sides of the wounds for most variables.Conclusion: CAP therapy showed promise for acute wound healing in rats, with minimal inflammation and scar formation. Further research is needed to optimize its use.